The Effect of Brand Equity on the Decision of BMT Al-Hijrah Madukoro Financing Customers in Sorong City - Hidayah, Nurul; Wangsi, Mitta Muthia; Aprilia, Nina (Jurnal Ar-Ribh, 2023)
Baitul Maal Tamwil (BMT) in its business focus contributes to encourage the economic empowerment of local communities. As a non-bank financial institution operating on sharia principles, it is a challenge for it to build brand equity and maximize its role to increase community financial inclusion. BMT Al-Hijrah Madukoro Branch, Sorong City, is an alternative microfinance institution that collects funds and distributes them into sharia financing products for the local community. This study aims to determine the effect of Brand Equity on customer decisions to take financing products at BMT Al-Hijrah Madukoro Branch, Sorong City. Research using Quantitative methods with convenience sampling techniques. The number of samples was 30 BMT Al-Hijrah financing customers. Data is analyzed with simple linear regression. The data was collected through a questionnaire on the google form link and distributed by BMT Al-Hijrah Madukoro Sorong City employees directly to their financing customers. The results show that there is an influence of Brand Equity on the Decision of BMT AL-Hijrah Financing Customers Madukoro Branch Sorong City